Mixed methods social network analysis theories and methodologies in learning and education - Froehlich, Dominik E.; Rehm, Martin; Rienties, Bart C. (Abingdon, Oxon Routledge, Taylor & Francis Group, 2020)
Mixed methods social network analysis brings together diverse perspectives from 42 international experts on how to design, implement, and evaluate mixed methods social network analysis (MMSNA). There is an increased recognition that social networks can be important catalysts for change and transformation.
MMSNA: an introduction of a tale of two communities / Dominik E. Froehlich, Martin Rehm, and Bart C. Rienties -- Why do mixed methods social network analysis? Mapping mixed methods approaches to social network analysis in learning and education / Dominik E. Froehlich ; Data collection for mixed method approaches in social network analysis / Manuel Längler, Jasperina Brouwer, and Hans Gruber ; Integrating units of analysis / Dominik E. Froehlich, Mathias Mejeh, Sarah Galey, and Judith Schoonenboom ; Visual methods and representations in mixed methods (and) social network research: a discussion / Peggy Shannon-Baker and Jonathan C. Hilpert ; Minding the gap between culture and connectivity: laying the foundations for a relational mixed methods social network analysis / Petter Törnberg and Anton Törnberg ; Ethnographic mixed methods social network analysis research: convergence, opportunities, and challenges / Marc Sarazin ; Mixed methods social network analysis to drive organizational development / Tuire Palonen and Dominik E. Froehlich ; Identity development through interactions in social networks: a complex systems approach / Judith Schoonenboom -- How do we do mixed methods social network analysis? Social network analysis and activity theory: a symbiotic relationship / Victoria L. Murphy, Allison Littlejohn, and Bart C. Rienties ; Exploring social relationships in "a mixed way": mixed structural analysis / Dominik E. Froehlich ; Unpacking the collegial network structure of beginning teachers' primary school teams: a mixed method social network study / Laura Thomas, Melissa Tuytens, Geert Devos, Geert Kelchtermans, and Ruben Vanderlinde ; Around and around: the concentric circles method as a powerful tool to collect mixed method network data / Sara Van Waes and Piet Van den Bossche ; Reflections about intersecting mixed methods research with social network analysis / Sinem Toraman and Vicki L. Plano Clark ; The role of knowing and valuing others' expertise in accelerating information exchange / Katerina Bohle Carbonell, Chris Marcum, Karen D. Könings, Patricia M. Stassen, Mien Segers, and Jeroen van Merriënboer ; Is mixed methods social network analysis ethical? / Maina Korer, Jenna Mittelmeier, and Bart C. Rienties ; Automation and the journey to mixed methods social network analysis / Dominik E. Froehlich, Christoforos Mamas, and Herwig W. Schneider ; Power to the people?! Twitter discussions on (educational) policy processes / Martin Rehm, Frank Cornelissen, Ad Notten, Alan Daly, and Jonathan Supovitz ; The PRICE of mixed methods social network analysis: toward an ethical process for MMSNA / Anthony J. Onwuegbuzie ; Powers and limitations of MMSNA: critical reflections and moving forward / Bart C. Rienties.
Includes bibliographical references and index.
Keywords: Social networks -- Research -- Methodology; Social sciences -- Network analysis